Webometric ranking of University of Zagreb and other world universities - Pavlina, Krešimir (Array, 2011)
This paper shows the shortcomings in the implementation of the algorithm used by Aguillo et al. for ranking of world universities, which negatively influenced ranking of 768 world universities, including the University of Zagreb. By correct application of the algorithm, ranking of University of Zagreb extremely improves, so the University of Zagreb is ranked 174th in the world (as opposed to 1355th by Aguillo et al.), 41st in Europe, 3rd in Central and Eastern Europe and 1st in Croatia.